The Institutional System Development of Law Contrary to the Closed Legislative List - Ghambaryan, Artur (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article examines the institutional framework for development that operates contrary to established legislative restrictions formulated as closed lists of appealable judicial acts. The theoretical framework employs Carl Schmitt’s concept of the "normal judge," with a focus on the institutional nature of judicial act contra legem. The author examines the judicial practice of the Republic of Armenia, where criminal courts demonstrate relative flexibility in applying closed lists—unlike civil and administrative courts, which adhere to a strictly formalistic approach. The study analyzes cases in which courts recognize acts not included in closed lists as appealable, as well as the approach of the Constitutional Court of the RA toward legislative gaps. The author criticizes the stance of the Constitutional Court of the Republic of Armenia, as articulated in its Decision ՍԴՈ-1476, according to which the Court is only authorized to review the constitutionality of legislative gaps (omissions) resulting from a defect (error) in legal regulation, whereas the legislator’s deliberate silence falls outside the scope of its jurisdiction